Bisnis Bank Syariah : Telisik Faktor Pengaruh Profit Distribution Management - Ardiani Ika Sulisytawati; Aprih Santoso; Annisa Ulfa (ITB AAS INDONESIA Surakarta, 2021)
The objective of this research to analyze the factors that influence the Profit Distribution Management on sharia banks in Indonesia. Sample of this research is sharia banks at listed in Bank Indonesia (BI) for the period of observation of 2016 - 2019. Data were collected using by purposive sampling method to Islamic Banks which publishes financial report consistently. The number of samples in this study are 8 Islamic Banks with 128 oberservation. Test analysis using assumption of classical test, hypothesis test, and multiple regression analysis. The result that variable proportion of non-investment financing, proportion of third party fund, bank age, effectiveness of third party funds, financing riskand third party funds significantly influence profit distribution management. The results of this study is expected that more sharia banks are capable of perform management and development of Islamic banks products based on results in accordance with the provisions of islamic sharia. Keywords: profit, investment financing, bank age, fund, risk